2019
DOI: 10.3390/socsci8040107
|View full text |Cite
|
Sign up to set email alerts
|

Framing ‘Friend’: Media Framing of ‘Man’s Best Friend’ and the Pattern of Police Shootings of Dogs

Abstract: The representation and framing of events by news sources plays a critical role in the way society comes to understand a given phenomenon. For example, the use of force by police officers against civilians is covered regularly by news media outlets. Far less widely examined, however, is the excessive use of force against companion animals or pets. Thus, to understand the ways in which police use of force against animals is framed in the media, we conducted qualitative content analyses of 189 print news articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It also follows that, through the process of framing, news media stories tend to favor the interpretations of events and social issues advanced by some claimsmakers rather than others (Ericson et al 1991; Fields and Newman 2020). Thacker Thomas and Vermilya (2019) suggest that that way news media frame incidents substantiates existing social hierarchies. The voices and views of claimsmakers most closely aligned with publicly favored frames are granted access to the news media and hence to elevated levels of attention.…”
Section: Framing Social Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also follows that, through the process of framing, news media stories tend to favor the interpretations of events and social issues advanced by some claimsmakers rather than others (Ericson et al 1991; Fields and Newman 2020). Thacker Thomas and Vermilya (2019) suggest that that way news media frame incidents substantiates existing social hierarchies. The voices and views of claimsmakers most closely aligned with publicly favored frames are granted access to the news media and hence to elevated levels of attention.…”
Section: Framing Social Problemsmentioning
confidence: 99%
“…The voices and views of claimsmakers most closely aligned with publicly favored frames are granted access to the news media and hence to elevated levels of attention. It is in this way that news media play a key role in shaping the definition of social events (Thacker Thomas and Vermilya 2019) and responses by policymakers, including incidents of police brutality and other forms of police‐involved violence (Lawrence 2000).…”
Section: Framing Social Problemsmentioning
confidence: 99%
“…Furthermore, extensive research has shown that framing the role, background, or origin of a robot can change how humans perceive and interact with it [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. This may also be effective with Aibo as, for example, in Western society, dogs are already framed as “man’s best friend” [ 43 ]. Researchers have indeed shown that trust in Aibo can be increased by priming the initial expectations through framing Aibo’s role and agency when introducing the robot to participants [ 44 ].…”
Section: Introductionmentioning
confidence: 99%